Public Procurement: Theory, Practices and Tools - Grandia, Jolien; Volker, Leentje (Springer Nature, 2023)
This upper-level open access textbook uses an interdisciplinary perspective to discuss the ‘what and why’ of public procurement, providing insight into the ‘how’ of contemporary procurement in the public sector. The authors use theories and exemplary practices to show the next generation of public procurement professionals how public value can be created via the acquisition of works, supplies, or services by organizations operating in the public domain. Perfectly tailored to university students in public administration, law, economics, or management and those in executive education, the book first describes and explains the public procurement process, the concept of public value, the legal context of procurement and how the procurement function is organized in public organizations. The book subsequently explains how a procurement policy can be developed and translated into a procurement strategy, how tenders can be organized, suppliers selected, and contracts designed and evaluated. A final discussion chapter addresses the changes and developments in public procurement and how public procurement is moving forward. The reader of this innovative and accessible book will therefore not only learn what public procurement entails, but also how they can become a professional change agent in the field of public procurement. Forward-thinking and comprehensive, this book offers ideal reading for anyone interested in public procurement.